Creative's commons nurturing the local creative economy through a visual arts and animation center - Pintor, Neal Armand S.; Ruby Teresa M. de Leon (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The Philippines possesses 40-years-worth of knowledge and skills in the animation
industry, but has failed to progress up the global creative economy value chain. While
a growing number of local schools have opened animation programs; the industry is
bottlenecked by the lack of a cohesive employment pipeline and creative intellectual
property. The study "Creatives' Commons: Nurturing the Local Creative Economy
through a Visual Arts and Animation Center" explores a shared service visual art
center that stimulates the common creative sensibilities between enthusiasts, students,
and professionals in the illustration, comics, and animation industry; and bridges it
with their social preferences. Data on the different visual creatives' conceptualization, production, and collaboration processes were obtained using qualitative research methods which include community engagement, surveys,interviews, observations; and is synthesized into the design of a commercial and civic space for the arts. By looking into the intersection of socially-interactive,
creativity-stimulating design, and the nuanced experiences of students, and visual
artists, who live with and without access to studio employment and facilities; this
study introduces a cohesive visual arts education and production facility in Naga
City, home of one of the country's pioneer animation schools. The center functions as
a preference-responsive third place for students and hobbyists to hone their craft, a
professional facility to accelerate original IP creative production, and an urban
landmark that opens more creative work opportunities outside of Metro Manila.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Art centers -- Naga City; Animations (visual works); Training centers for animators